The European added value of the recovery and resilience facility: An assessment of the Austrian, Belgian and German plans - Francesco Corti; Daniel Gros; Tomás Ruiz De La Ossa; Alessandro Liscai; Tamas Kiss-Galfalvi; David Gstrein; Elena Herold; Mathias Dolls; Clemens Fuest (CESifo GmbH, 2022)
This paper conducts an in-depth analysis of the National Recovery and Resilience Plans (NRRPs) of Austria, Belgium, and Germany. Exploiting a detailed database that covers all the investments and reforms included in the NRRPs and building on insights from semi-structured expert interviews, we study their alignment with EU objectives, the additionality of the spending, and the cross-border effects. We find that all three NRRPs are well aligned with the objectives defined in the RRF Regulation but differ greatly in terms of additionality. Cross-border projects are only of limited importance. We finally highlight some missed opportunities for other cross-border projects.
Keywords: 330